Anti-osteoporotic effects of Salvia miltiorrhiza Bunge EtOH extract both in ovariectomized and naturally menopausal mouse models. (10th August 2020) - Lee, Sung Ryul; Jeon, Hyelin; Kwon, Jeong Eun; Suh, Heeju; Kim, Byung-Hak; Yun, Min-Kyu; Lim, Ye Ji; Kang, Se Chan
Abstract: Ethnopharmacological relevance: Salvia miltiorrhiza is a traditional oriental medicine widely used for preventing and treating disorders of the liver, menstrual, and blood circulation systems. Osteoporosis, loss of bone with age and/or estrogen deficiency, is an important causal factor of fracture. S. miltiorrhiza extract has been used to alleviate dysmenorrhea and painful osteoarthritis. Aim of the study: This study was performed to investigate the anti-osteoporosis activity of the Salvia miltiorrhiza ethanol extract (SME) in osteoporosis-prone conditions: ovariectomized (OVX) and naturally menopaused (NM) ICR mice. Materials and methods: Anti-osteoporotic potentials of SME (50–200 mg/kg) were evaluated based on bone mineral density using microCT analysis, biochemical parameters, and changes in the gene expressions involved in bone resorption. Results: SME ameliorated the loss of trabecular bone both in OVX and NM mice. SME was effective in correcting aberrant levels of RANKL, osteocalcin, and BALP, which are critically involved in bone resorption. In addition, SME suppressed the expression of TRAF6 and NFATc1, which play a role in osteoclast differentiation. Conclusions: SME suppressed the loss of trabecular bone via suppressing bone resorption and osteoclast differentiation both in OVX and NM mice. SME is likely to be developed as a therapeutic agent for osteoporosis. Graphical abstract: Image 1